"Slide Taken Out of Tree in Fatal Park Crash" - Tinney, Jack (Philadelphia Evening Bulletin, 1958)
"Automobile is wrecked after crashing into a tree on Greenland drive near Robin Hood Dell in Fairmount Park. A passenger, Leroy Knighten, 50, was killed. Driver Melvin Jeffcoat, 19, was approaching the Strawberry Mansion Bridge when he lost control of the vehicle." With clipping